2022
DOI: 10.1002/asmb.2683
|View full text |Cite
|
Sign up to set email alerts
|

Optimal time‐consistent social health insurance and private health insurance strategy under a new health insurance framework

Abstract: A new continuous‐time health insurance framework is proposed to simultaneously determine the optimal social health insurance strategy and optimal private health insurance strategy. The social health insurance can cover both the expenditures of general illnesses and critical illnesses, while the private health insurance only covers the expenditure of critical illnesses. To reflect the inevitable connection between critical illnesses and general illnesses, we assume that the number of critical illnesses and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 40 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…Method 2, method of deleting explanatory variables, that is, deleting the value and appreciation rate of capital (CRNA) in explanatory variables of the model. Another set of estimated results is shown in column (3). By comparing columns ( 1) and (3) in Table 7, it can be found that, compared with the regression of "PW+PCSE…”
Section: Robustness Testmentioning
confidence: 98%
See 2 more Smart Citations
“…Method 2, method of deleting explanatory variables, that is, deleting the value and appreciation rate of capital (CRNA) in explanatory variables of the model. Another set of estimated results is shown in column (3). By comparing columns ( 1) and (3) in Table 7, it can be found that, compared with the regression of "PW+PCSE…”
Section: Robustness Testmentioning
confidence: 98%
“…(2) In terms of the individual variables, divorce, non-urban residential areas, apartment type of housing, non-ownership of homes, and bad relationship with siblings increased the surrender rate. (3) In terms of the financial variables, low income, low expenditure, the existence of children that incurred child care expenditure, not expecting to bequest from spouse, not holding public health insurance, and expecting to benefit from a retirement pension increased the surrender rate.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Since the commercial health insurance industry of China resumed operation in 1982, its business scale has become increasingly large and its development speed has advanced rapidly [ 2 , 3 , 4 ]. In terms of the number of companies, this increased from 1 in 1982 to 164 in 2020; in terms of premium scale, this increased from CNY 57.4 billion in 2009 to CNY 817.3 billion in 2020, and the annual compound growth rate reached 24.78%, higher than the life insurance premium income of 10.22% and accident insurance premium income of 14.55% in the same period.…”
Section: Introductionmentioning
confidence: 99%
“…It may be very difficult to choose an appropriate stochastic process to predict dynamic illness expenditure. The Poisson process may be a good choice; recently, [22] adopted the Poisson process to describe the number of illnesses, and used the compound Poisson process to describe the cumulative expenditures of illnesses. Nevertheless, this method cannot reflect the influence of health status on illness expenditure.…”
Section: Introductionmentioning
confidence: 99%